ANALISIS PERILAKU MEROKOK PADA PEREMPUAN MUDA SEBAGAI BENTUK COPING STRES - Anisya; Sherina Betharia Silaban; Nova Novita Siregar; Citra Nanda Purba; Sani Susanti; Michael Yudha Pratama (STKIP Subang, 2026)
Smoking behavior among young women is a social phenomenon influenced by psychological and social factors. This study aims to analyze smoking behavior among young women as a form of stress coping based on a case study of an informant with the initial “AM”. The research uses a qualitative descriptive approach through in-depth interviews. The findings show that smoking behavior is influenced by family conditions, economic burden, psychological state, and social environment. In addition, the behavior emerges as an individual response to daily life pressures. In conclusion, smoking behavior is used as a temporary coping mechanism in dealing with life stress